PENGARUH PERSON ORGANIZATION FIT DAN WORKPLACE SPIRITUALITY TERHADAP TURNOVER INTENTION DENGAN AFFECTIVE COMMITMENT SEBAGAI VARIABEL INTERVENING DAN GENERASI MILLENNIAL SEBAGAI MODERASI(STUDI KASUS PT. BANK TABUNGAN NEGARA) - Nevi Nevada (UNUSA Press, 2021)
This study aims to determine the effect of person organization fit and workplace spirituality on turnover intention through affective commitment as an intervening variable. Also, to determine the relationship between person organization fit on turnover intention moderated by millennials generation, Samples in this study are employees of PT. Bank Tabungan Negara, Tbk. , total of 100 respondents. This type or research is explanatory with quantitive methods. The sampling technique used is nonprobability sampling with purposive sampling, namely the technique of sampling data source with certain considerations. This study uses a survey method using a questionnaire in data collection and processedusing Partial Least Squares. The results of the testing of hypothesis indicate that there is a negative effect of person organization fit on turnover intention, There is a negative effect of workplace spirituality on turnover intention. There is a positive effect of person organization fitand workplace spirituality on affective commitment. There is negative effect of affective commitment on turnover intention. There is an effect of person organization fit and workplace spirituality on turnover intention through affective commitment. There is a relationship between person organization fit on turnover intention moderated by millennials generation.